Tinjauan Etika Bisnis Islam pada Jasa Makelar Jual Beli Mobil Bekas melalui Media Sosial - Indah Nur Fauziah; Nanik Eprianti; Iwan Permana (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Business transaction activities sometimes require mediators or brokers, especially in buying and selling transaction activities, at this time it also occurs in the business sector of buying and selling used cars through social media. In practice, brokers are often not transparent in offering cars to consumers by not providing objective information regarding the actual condition of the vehicle, so that consumers feel disadvantaged. Which indicates that this raises many potential violations in terms of Islamic business ethics. Based on this, this study aims to determine and analyze the mechanism of brokerage services in buying and selling used cars through social media, and to find out the review of Islamic business ethics on brokerage services in buying and selling used cars through social media. The research method used is analytical descriptive to review the suitability of the broker's service mechanism in buying and selling used cars through social media with the principles of Islamic business ethics. The results of the study show that the mechanism of brokerage services in buying and selling used cars through social media, especially what happens on the FB account of Bandung X Used Car Buying and Selling is carried out in two ways which provide opportunities for the broker to get fees from both the seller and the buyer, and the brokerage service mechanism in buying and selling used cars through social media, especially what happened to the Bandung X Used Car Buying and Selling FB account, are not in accordance with the principles of Islamic business ethics, especially from the aspect of the principles of justice, the principle of free will, the principle of responsibility, and the principle of honesty. Abstrak. Kegiatan transaksi bisnis terkadang memerlukan mediator atau makelar khususnya dalam kegiatan transaksi jual beli pada saat ini juga terjadi pada sector bisnis jual beli mobil bekas melalui media sosial. Pada praktiknya, pihak makelar seringkali tidak transparan dalam menawarkan mobil kepada konsumen dengan tidak memberikan keterangan secara objektif terkait kondisi kendaraan yang sebenarnya, sehingga konsumen merasa dirugikan. Yang mana hal ini terindikasi banyak menimbulkan potensi pelanggaran dari sisi etika bisnis Islam. Berdasarkan hal tersebut, maka penelitian ini bertujuan untuk mengetahui dan menganalisis mekanisme jasa makelar dalam jual beli mobil bekas melalui media sosial, dan untuk mengetahui tinjauan etika bisnis Islam pada jasa makelar dalam jual beli mobil bekas melalui media sosial. Metode penelitian yang digunakan adalah deskriptif analitis untuk meninjau sejauhmana tingkat kesesuaian mekanisme jasa makelar dalam jual beli mobil bekas melalui media sosial dengan prinsip-prinsip etika bisnis Islam. Hasil penelitian menunjukkan bahwa mekanisme jasa makelar dalam jual beli mobil bekas melalui media sosial khususnya yang terjadi pada akun FB Jual Beli Mobil Bekas Bandung X dilakukan melalui dua cara yang memberikan peluang pihak makelar mendapatkan fee dari penjual maupun pembeli, dan mekanisme jasa makelar dalam jual beli mobil bekas melalui media sosial khususnya yang terjadi pada akun FB Jual Beli Mobil Bekas Bandung X belum sesuai dengan prinsip-prinsip etika bisnis islam terutama dari aspek prinsip keadilan, prinsip kehendak bebas, prinsip tanggung jawab, dan prinsip kejujuran.